Enhancing awareness of STIs and cervical cancer among husbands in an urban slum of Mumbai, India: a comparative study focusing on General, OBC and SC/ST/NT population - Naik, D. D.; Donta, Balaiah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Globally, cervical cancer is one of the most common cancers among women, 80 percent of cervical cancer cases present with an advanced stage of the disease when cure is impossible. This may be due to lack of awareness and knowledge, and lack of access to proper treatment including screening facility. Involvement of husband for understanding and supporting the wife may be more effective in reproductive health related matters. Methods: An intervention study was undertaken in an urban slum of Mumbai with the objectives to investigate the awareness, knowledge and perceptions about STIs and cervical cancer and to identify programme strategies contributing to effective participation of husbands in three different categories. Baseline data was obtained from 1020 married men followed by interventions for 18 months and endline data was collected from 1013 married men to evaluate the impact of intervention. Descriptive statistics and Chi-square test was used for data analysis. Results: The results indicate significant increase in awareness about STIs, cervical cancer and Pap smear with low awareness about symptoms, abnormal discharge from vagina and abnormal vaginal bleeding in all the three groups. Conclusions: Study concludes that intervention strategy adopted at community as well as clinic level can play better role as a source of information of STIs and cervical cancer. Similar changes observed in all three categories suggest, programmes need to focus on general population rather than specific categories in a metropolitan city like Mumbai as population in urban slums of Mumbai is ethnically mixed in nature.